Caractéristiques des Caséines du Lait de Vache, Effet de la Température - MAZZOUZI, OUSSAMA (My University, 2021)
The cattle milk is very busy in Algeria, in order to meet the needs of the population which is constantly increasing and who consumes the milk in the fresh state or transformed many are the manufacturers who transforms the milk products derived mainly cheese. For the latter case, it established that only milks possessing αs1 exprimée avec fort pourcentages1 casein expressed with a high percentage could give rise to the manufacture of cheeses. The strong tendency of the main caseins (as "aS2, f3 and K) to associate in aqueous solution is well known and is largely explained by the high content of non-polar amino acids. form these “quaternary” structures is quite divergent: the association of the as, and aS2 caseins leading to consecutive oligomers, while f3 and K form micelles with a fairly high degree of association. The ability of milk to withstand high temperatures is an important technological property. Increasing the thermal stability of milk is desirable in several food applications in order to ensure the shelf life of sterilized milks by preventing gelation in storage (Singh, 2004)
Keywords: raw milk, caseins, heat treatment